Hidden strike = 狂怒沙暴 [videorecording (DVD)] - Amel, Arash; Cheng, Long, 1954-; Cena, John; Jiang, Wenli, 1966- (Beijing Talent International Film Co. Ltd, 2023)
Two elite soldiers must escort civilians through a gauntlet of gunfire and explosions.